The problem of studying the theories of social contract in the domestic philosophical tradition - Lytvynenko, Nataliia (Actual Problems of Mind, 2017)
The article raises the problem of studying the concepts of social contract in the domestic philosophical tradition, formulates an idea of the limited approaches to the study of these theories in both the soviet and modern philosophical tradition, justifies the necessity of complex analysis of modern contractual concepts in view of their classical predecessors, which will enable to systematize the theories of social contract and determination of the directions and prospects of their development on the world philosophical ground.